Fertilização fosfatada de cultivares de cana-de-açúcar em regimes hídricos: produção, composição bromatológica e desempenho de ovinos - Faria Júnior, Oscar Lopes de (2015)
In the period between harverts in the cerrado region, the production of great volumes of feed, is important for animal productivity, and being that sugar cane is a viable alternative, from there arises the necessity of avaluating the available cultivating for animal supplements. The objective of this study was to evaluate the productions, bromatologic composition and animal results of two cultivars (cv) of sugar cane (IAC 86-2480 and SP 80-0155) with increasing doses of phosghorous (0, 60, 120 and 180 kg P2O5 ha-1) in differing water systems (dry and irrigated). To evaluat these treatments the statiscal delineation of completely blocks was used, with three repetitions. The data were submitted to an alalysis of variance and the averages were compared to a 5% of probability (Tukey). The stalls collected were delimited thus: production green mass (PGM), concetrations of saccharose (%pol), production of dry mass (PDM), fiber in acid detergent (FAD), fiber in neutral detergent (FND, the relationship FND/%pol, and tillering. The tillering differed from the dry to the irrigated from 5.45 to 14.54 and from 6.75 to 13.68 units m-1 in the cultivars IAC and SP, respectively. In the avaliation PGM the cv SP was that which presented a better response with application of increasing doses of phosphorus (in dose 180 kg P2O5 ha-1), reaching greatest productivity with 122.25 and 173.97 t ha-1, for dry and irrigated, respectively. As such, the cv IAC presented in dryness a better PGM (91.88 t ha-1) in the dose of 120 kg P2O5 ha-1and under irrigation (168 t ha-1) in the dose 180 kg P2O5 ha-1. The PDM differed in function of the doses of phosphorus and presented the greatest PDM (39.16 and 43.21 t ha-1) in the doses of 120 e 180 kg P2O5 ha-1 for the cv IAC and SP, respectively. The %pol difered between cultivars, doses and water sistems. Under dryness the greatest concentração %pol (22.43 and 22.42) occurred in the doses 60 e 120 kg P2O5 ha-1 for the cultivars IAC e SP, respectively. Under irrigation the greatest concentration %pol (22.49 and 22.74) occurred in the dose of 120 P2O5 ha-1 for the cultivars IAC and SP. The quantities of FAD differed with the water treatment; the cv IAC presented the lowest values with irrigations (50.13%) and the cv SP with dryness (51.38). The smallest quantities of FAD were in the doses of 120 kg P2O5 ha-1 (34.88%) and 60 kg P2O5 ha-1 (33.35%). The lowest relationship FAD/%pol (2.3) was obtained from the doses 180 and 60 kg P2O5 ha-1 for the cv IAC and SP respectively. With the objective of avaluating the performance and the characteristics of the carcasses of ovines, the cv IAC and SP were utilized with two levels of concentrates, 50 and 70% DM (SP50, IAC50, SP70 and IAC70). The experimental design was a complet block design and factorial arrangeament with six repetitions. The data were submitted to analysis of variance and the averages compared ar 5% (Tukey). The cv SP showed great carcass yield and average daily weigth gain than cultivars IAC. The level of concentrate of 70% showed the greater average daily weigth gain.